Parents: our most important resource - Shapiro, Leah; Olenick, Rhoda; Woronko, Ula; General Learning Communications (Firm); Magna Systems (Barrington, IL. : Magna Systems Inc., 2004)
This module explains the many different ways teachers and parents communicate to assess the development of the child. Some of the ways are: discussing the developmental history form at the initial interview, sharing observations with the parents and helping the child to seperate at the beginning of the year, beginning and end-of the year home visits, on-going communication when parents drop off and pick up children, conferencing with parents at least two times a year, conferencing with parents on an as-needed basis, teacher-parent room meetings to explain the assessment process and parent manuals
Writer/Educational consultant, Leah Shapiro ; Producer, Ula Woronko
Content consultant/Narrator, Rhoda Olenick
DVD
No Master.
Keywords: Education, Preschool -- United States -- Evaluation; Education, Primary -- United States -- Evaluation